Analisis Peran Manajerial pada data keuangan PT HM Sampoerna - Vitria Ramdoni; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the financial performance of PT HM Sampoerna Tbk over the 2019–2023 period using liquidity ratios (current ratio, quick ratio, cash ratio) and profitability ratios (net profit margin, return on assets, return on equity). The research employs financial ratio analysis compared to industry benchmarks. The findings indicate that the current ratio in 2023 is 1.72, below the industry standard of 2.00. The cash ratio is notably low at 0.12, significantly under the standard of 0.50. Profitability indicators also show a decline, with net profit margin at 7%, return on assets at 14.6%, and return on equity at 27.1%, all below industry benchmarks. In conclusion, PT HM Sampoerna Tbk faces challenges in liquidity and profitability management, necessitating improvements in cash flow and operational efficiency to maintain competitiveness in the industry.